2020
DOI: 10.1136/heartjnl-2019-316515
|View full text |Cite
|
Sign up to set email alerts
|

Variations in knowledge, awareness and treatment of hypertension and stroke risk by country income level

Abstract: ObjectiveHypertension is the most important modifiable risk factor for stroke globally. We hypothesised that country-income level variations in knowledge, detection and treatment of hypertension may contribute to variations in the association of blood pressure with stroke.MethodsWe undertook a standardised case-control study in 32 countries (INTERSTROKE). Cases were patients with acute first stroke (n=13 462) who were matched by age, sex and site to controls (n=13 483). We evaluated the associations of knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
(30 reference statements)
4
22
0
3
Order By: Relevance
“…KCVDs increased by 1.121 times in those with BP awareness, and AoBP increased by 1.076 times as KCVDs increased, suggesting KCVDs and AoBP have a significant positive influence on each other. Additionally, the factors related to KCVDs were consistent with previous studies [16][17][18][19]24,26,41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…KCVDs increased by 1.121 times in those with BP awareness, and AoBP increased by 1.076 times as KCVDs increased, suggesting KCVDs and AoBP have a significant positive influence on each other. Additionally, the factors related to KCVDs were consistent with previous studies [16][17][18][19]24,26,41].…”
Section: Discussionsupporting
confidence: 90%
“…In HTN patients, when the BP level exceeded 150 mmHg (versus > 120 mmHg), it increased the first ischemic stroke incidence by 1.6 times [23]. Additionally, stroke incidence was 1.8 times higher in hypertensive patients who never had a BP measurement throughout their lifetime [24]. Patients in Asia did not view HTN as a serious condition and ignored high BP because HTN has no overt physical symptoms [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies have reported global and regional variations in the prevalence, awareness, treatment, and control of hypertension [ 5 , 6 , 7 , 8 ]. For example, in the Middle East, findings from the Prospective Urban Rural Epidemiology (PURE) study showed that the prevalence of hypertension was high (33%) and that the lack of awareness (49%) was also high, while BP control was only 19% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…OSA refers to the partial or complete collapse of the upper airway during sleep, resulting in reduced or absent (or apnea) airflow lasting for 10 s [ 123 ]. Many OSA patients are highly likely to show cardiovascular or cerebrovascular diseases, as OSA is also associated with hypertension, a direct risk factor of stroke [ 120 , 127 , 128 , 129 ]. OSA is also associated with fibrinogen levels, a key independent risk factor for myocardial infarction and vascular diseases [ 130 , 131 ].…”
Section: Associations Between the Factors Influencing Cognitive Decli...mentioning
confidence: 99%